The significance of values in selecting political leadership among the post-NEP Malay Middle class - Hairol Anuar Mak Din,; Zakaria Stapa,; Ahmad Munawar Ismail, (Universiti Kebangsaan Malaysia, 2013)
This research aims to investigate the influence of values among post-NEP Malay Middle class, particularly in the segment of the political leadership election. The process of conducting this research was using quantitative research design. 544 respondents were participated in this research, using purposive sampling based on the table of sample determiner by Krejie & Morgan. The reliability and validity of the questionnaire were validated by the appointed specialist. The validated instrument was thoroughly analyzed by identifying the internal consistency of the items used: 1) Partial separation method using the SPSS program, and 2) the value of Correlation Coefficient and internal consistency method of Alpha Cronbach, the Alpha value. The data of this research were statistically analyzed using descriptive and inferential percentage, mean, and standard deviation. Findings showed that: 1) the understanding of the concept among the respondents; mean=4.02/ standard deviation=.354 that marked the highest interpretation level, 2) the influence of value in life; mean=3.35/standard deviation=.439, that marked an average interpretation level, 3) the role of value in the political leadership; mean=3.13/standard deviation=.464, that marked an average interpretation level, and 4) the role of value as the main factor; mean=3.81/standard deviation=.563, that marked an average interpretation level. Based on the findings of this research, it is hoped that it can help researchers and mass in obtaining a valid and reliable source of knowledge, thus giving an answer to the problems outlined in the hypotheses of this research. Finally, it explains the importance of contributing value and subsequently influenced the selection of political leadership among the post-NEP Secondary Malay Middle Class.